A comparison of Australian chronic disease prevalence estimates using administrative pharmaceutical dispensing data with international and community survey data - Purkiss, Shaun Francis (Int J Popul Data Sci, 2020)
INTRODUCTION: Chronic disease (CD) is a leading cause of population mortality, illness and disability. Identification of CD using administrative data is increasingly used and may have utility in monitoring population health. Pharmaceutical administrative data using World Health Organization, Anatomic Therapeutic Chemical Codification (ATC) assigned to prescribed medicines may offer an improved method to define persons with certain CD and enable the calculation of population prevalence. OBJECTIVE: To assess the feasibility of Australian Pharmaceutical Benefits Scheme (PBS) dispensing data, to provide realistic measures of chronic disease prevalence using ATC codification, and compare values with international data using similar ATC methods and Australian community surveys. METHODS: Twenty-two chronic diseases were identified using World Health Organization (WHO) formulated ATC codes assigned to treatments received and recorded in a PBS database. Distinct treatment episodes prescribed to individuals were counted annually for prevalence estimates. Comparisons were then made with estimates from international studies using pharmaceutical data and published Australian community surveys. RESULTS: PBS prevalence estimates for a range of chronic diseases listed in European studies and Australian community surveys demonstrated good correlation. PBS estimates of the prevalence of diabetes, cardiovascular disease and hypertension, dyslipidemia, and respiratory disease with comparable Australian National Health Survey in older adults showed correlations of between (r = 0.82 - 0.99) and a range of percentage error of -11% to 59%. However, other conditions such as psychological disease and migraine showed greater disparity and correlated less well. CONCLUSIONS: Although not without limitations, Australian administrative pharmaceutical dispensing data may provide an alternative perspective on population health and a useful resource to estimate the prevalence of a number of chronic diseases within the Australian population.